Perspectives of Faculty on Student Evaluations of Teaching at an Anglophone Caribbean University - Mervin E. Chisholm (Adult Education Research Conference, 2014)
Student evaluations of teaching (SET) remain the most prominent and the primary source of data used to evaluate classroom teaching at many colleges and universities internationally (Cashin, 1999; Felten, Little & Pingree, 2004; Spooren, Brockx & Mortelmans, 2013; Zabaleta, 2007). This is also the case in the Anglophone Caribbean and at the leading research institution in the Anglophone Caribbean; the University of the West Indies, student evaluations of teaching remain the only method of the evaluation of the teaching of the faculty. Generally, from time to time, these evaluations are experienced as intrusive, invasive, frustrating and frightening (Ory, 2001). There are instances where faculty members become defensive and extremely protective of themselves and their pedagogy when poor evaluation results are communicated to them. Fink (2008) has asserted that the widespread use of SET is not driving instructional improvement; instead it is creating widespread cynicism about teaching evaluations.